1998
DOI: 10.1002/hlca.19980810542
|View full text |Cite
|
Sign up to set email alerts
|

3‐Hydroxy‐2‐cyanoalk‐2‐enamides, and 2‐Cyano‐2‐(tetrahydrofuran‐2‐ylidene)‐ and 2‐Cyano‐2‐(tetrahydropyran‐2‐ylidene)acetamides: Synthesis, structure, and solvent‐dependent (Z)/(E)‐isomerism

Abstract: Dedicated to Professor D. Srehuck on the occasion of his 60th birthday 3-Hydroxy-2-cyanoalk-2-enamides, and 2-cyano-2-(tetrahydrofuran-2-ylidene)-and 2-cyano-2-(tetrahydropyran-2-y1idene)acetamides with N-alkyl and N-aryl substituents have been synthesized in three steps from cyanoacetic acid. Their conformations were investigated by X-ray crystallography and 'H-NMR ROESY spectroscopy at room temperature. The enolic compounds 1-3 adopt an extended conformation stabilized by a strong intramolecular 0 -H ... O=C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As we have mentioned in the introductory section, previous studies on the structure of teriflunomide 2 suggested that compound 2 and some of its analogues existed mainly in a Z configuration stabilized by a strong intramolecular hydrogen bond (Scheme 1 ) [ 30 32 ]. Other reports, both experimental and theoretical, pointed out that the active form of teriflunomide was the Z configuration lacking the internal hydrogen contact [ 14 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have mentioned in the introductory section, previous studies on the structure of teriflunomide 2 suggested that compound 2 and some of its analogues existed mainly in a Z configuration stabilized by a strong intramolecular hydrogen bond (Scheme 1 ) [ 30 32 ]. Other reports, both experimental and theoretical, pointed out that the active form of teriflunomide was the Z configuration lacking the internal hydrogen contact [ 14 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that teriflunomide 2 also interacts with arginine through a water molecule in the active site of DHODH [ 30 32 ]. To examine whether this is a significant feature, we optimized the adducts of compound 2 with water, in which a single molecule of water interacted separately with the OH, NH, and CO groups of 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Cyanoacetamides were prepared by applying methods described in the literature, usually by heating an amine with ethyl cyanoacetate [7] (Method A) or by condensation with cyanoacetic acid in the presence of diisopropyl carbodiimide [8,9] (Method B).…”
Section: Methodsmentioning
confidence: 99%